Визначення бізнес-процесу з точки зору корпоративної соціальної відповідальності - Брінь, Павло Володимирович; Вашкевич, Ілля Ігорович (Видавничий дім "Гельветика", 2020)
У статті запропоновано методологічні основи аналізу внеску бізнес-процесу в результативність підприємства з урахуванням корпоративної соціальної відповідальності. У дослідженні підприємство розглянуто авторами як сукупність бізнеспроцесів, кожен з яких бере участь у формуванні кінцевої інтегральної результативності підприємства загалом. Розглянуто основні характеристики бізнес-процесів. Однією з тенденцій менеджменту 20-х рр. XXI століття є активізація використання концепції корпоративної соціальної відповідальності, при цьому, на відміну від поглядів XX століття, що розглядають соціальну відповідальність підприємств виключно як філантропічну діяльність, нині корпоративна соціальна відповідальність все частіше використовується як засіб підвищення конкурентоспроможності. Авторами запропоновано методологічні основи врахування внеску бізнес-процесу з урахуванням корпоративної соціальної відповідальності, що має сприяти підвищенню конкурентоспроможності підприємства загалом.

The article offers methodological bases for the analysis of the contribution of a business process to corporate social responsibility of the company. In the study a company is considered as a set of business processes; each business processes participates in the formation of the final performance of the enterprise as a whole, the article also considers the main characteristics of business processes. One of the trends in the management of the XXI century is to intensify usage of the concept of corporate social responsibility, and in contrast to the views of the XX century, which consider corporate social responsibility as only philanthropic activity, now the usage of corporate social responsibility concept is considered as a powerful instrument of competitiveness increasing. In the article the authors propose a methodological basis for evaluating of contribution of a business process to corporate social responsibility, which in turn should help increase the competitiveness of the enterprise. Corporate social responsibility means responsible attitude of any company to its product or service, to consumers, employees; participation in solving the most important social problems. In today’s world running business in socially responsible way is a common rule which is followed by a big number of large, medium and even small companies around the world. Taking into account the extraordinary social and economic benefits that are an outcome from the social responsibility of business, issues of its development belong to the sphere of special attention of scientists of many countries and international organizations. Manifestation of this attention is the development of corporate social responsibility standards and measures to stimulate business to socially responsible activities. When analyzing the enterprise as a set of business processes, one of the most important issues is to assess the contribution of every business process to the overall performance of the enterprise. It can be assessed by considering the contribution of the business process to the total value added and to the key success factors. The results of evaluating of business process’s contribution to the performance of the enterprise can be used as an information base for decision-making process regarding reengineering, outsourcing of business processes, etc.
Defining the business process in terms of corporate social responsibility
Keywords: управління; цілі; стратегія; конкурентоспроможність підприємства; business process management; corporate social responsibility; objectives; strategy; enterprise’s competitiveness